Design of a helium-6 production target for the iThemba LABS Radioactive-ion Beam Facility - Davis, Lance Garth (University of the Western Cape, 2019)
>Magister Scientiae - MSc === It is well known, that there is a severe lack of information available pertaining to neutron rich nuclei, specifically of those nuclei with mass numbers ≥ 60. These neutron rich nuclei are not easy to access in current experimental facilities or be produced with sufficient yield to allow for it to be studied. In order to expand our understanding of nuclear physics by studying the properties and characteristics of these nuclei, the development of new facilities producing Radioactive-ion Beams (RIBs) is required. The applications for RIBs are wide, allowing for deeper investigations into the properties of nuclei, their interactions and the manner in which they were formed in the early universe. Additionally, there are various interdisciplinary fields such as medicine, biology and material science in which RIBs can be utilized as a driving mechanism for new research and technological innovation. The iThemba Laboratory for Accelerator Based Sciences (iThemba LABS), South Africa, has proposed a new facility for the production and acceleration of radioactive-ion beams (RIBs). The RIB Project is to be developed in sequential phases and would produce a range of neutron-rich isotopes for low-energy materials science and nuclear physics research. Of specific interest, is the production of the Helium-6 isotope (6He), for its potential applications in various areas of nuclear physics research. The aim of this research work was to design, model and optimise a RIB production target capable of producing high intensity 6He beams, guided by the characteristics of the primary proton beam available for use at iThemba LABS. This research work/design study is however limited, due to the absence of experimentally measured and verified 6He cross section data for proton induced reactions on the proposed target materials (Graphite and Boron Carbide). However, best-estimate approaches were adopted through the use of validated computer codes. Additionally, all 6He yield results are presented as in-target yields, as this study did not cover the diffusion (isotope release) efficiency of the target systems in question. Three RIB production targets types were investigated using Graphite, Boron Carbide and Beryllium Oxide as potential target materials. Following numerous optimisation processes, a Boron Carbide RIB target was converged upon, proving to be suitable for the production of high intensity 6He beams at iThemba LABS, by meeting the material thermal and mechanical limiting criteria for operation. This target system was found to produce an in-target 6He yield rate of 2 ~ 3 x 1011 6He/s, considered sufficient for experimental application at iThemba LABS.